1963
DOI: 10.1103/physrevlett.11.52
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Spin and Decay Parameters of Fermion States

Abstract: There is a difference of a factor 64 between our calculation and that of Riazuddin and Fayyazuddin. We believe that the latter authors have used a wrong definition of A differing by a factor of 8 from the conventional one, so that we have to multiply their expression by 64. 8 S. Coleman and S e L. Glashow, Phys. Rev. Letters 6>, 423 (1961). Equation (13) has been also noted by E. C. G. Sudarshan (private communication). We may remark that we can estimate y by another formula, y = (l/2v r 3*)[m 2 (7r 0 ) + 3w 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1964
1964
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…More recently, BABAR reported evidence for J P = 1/2 − for the Ξ(1690) by analyzing the Legendre Polynomial moments of the Ξ − π + system in the decay Λ + c → Ξ − π + K + [7]. Clear evidence for Ξ(1820) was observed in the K − Λ mass spectrum from a sample of 130±16 events in K − p interactions [8], and the J = 1/2 assumption was ruled out by using the Byers and Fenster technique [9]. Ten years later, a CERN-SPS experiment indicated that Ξ(1820) favors negative parity in the case of J = 3/2 [10].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, BABAR reported evidence for J P = 1/2 − for the Ξ(1690) by analyzing the Legendre Polynomial moments of the Ξ − π + system in the decay Λ + c → Ξ − π + K + [7]. Clear evidence for Ξ(1820) was observed in the K − Λ mass spectrum from a sample of 130±16 events in K − p interactions [8], and the J = 1/2 assumption was ruled out by using the Byers and Fenster technique [9]. Ten years later, a CERN-SPS experiment indicated that Ξ(1820) favors negative parity in the case of J = 3/2 [10].…”
Section: Introductionmentioning
confidence: 99%
“…Excited cascades can be investigated in reactions such as γp → K + K + Ξ − (1820), Ξ − (1820) → K − Λ, Λ → pπ − . This would allow the determination of the spin and parity of the observed excited cascade states [25]. The polarization of ground state Ξ can also be measured with uncertainties sufficiently small to constrain production models that currently can not separate the contributions of various intermediate hyperon resonances.…”
Section: ω − Photoproduction and The Very Strange Experiments At Clas12mentioning
confidence: 99%
“…The narrowness allows one to determine the spin and parity by a Byers-Fenster [22] or Button-Shafer analysis, rather than a cumbersome partial wave analysis.…”
Section: Program Iic: "Measurements Of Cascade Photoproduction With Tmentioning
confidence: 99%